Different light acclimation strategies of two coexisting tree species seedlings in a temperate secondary forest along five natural light levels - Zhang, Min; Zhu, Jiaojun; Li, Mingcai; Zhang, Guangqi; Yan, Qiaoling (Forest ecology and management, 2013)
•Light regulation mechanisms for two species natural regeneration are discussed.•Silvicultural measures to improve two species regeneration are proposed.•The coexistence mechanism of the two species is analyzed. To understand how temperate coexisting tree species acclimate to natural light levels, seedlings of two coexisting species, Pinus koraiensis Sieb. et Zucc. and Quercus mongolica Fisch., were transplanted to five light levels (100%, 20%, 10%, 5%, and 1%) under natural forest stands. The survival/growth rates, nonstructural carbohydrate (NSC) concentrations and pools in each plant organ of the two species seedlings were monitored in two consecutive years. The survival rate and relative growth rate (RGR) of both species peaked at the 100% light level. No seedlings of both species survived at the 1% light level. The NSC concentration varied insignificantly with light levels in the roots of Q. mongolica and the stems of both species in 2010, while the NSC concentration and pool decreased with light reduction for both species in 2011. With a light level decrease from 20% to 5%, Q. mongolica showed insignificant differences, but P. koraiensis exhibited a significant decrease in survival rate and NSC levels. The survival rates of P. koraiensis and Q. mongolica seedlings were positively and significantly related to the NSC concentration in leaves (r1=0.9898) and NSC concentration in roots (r2=0.9976), respectively. These results suggested that: (1) full sunlight was the optimum light environment for the initial survival and growth of both tree species; (2) low light induced carbohydrate deficiency, which might be the key factor resulting in seedling mortality in forest understory; (3) different NSC allocation patterns in response to light alteration might promote the coexistence of P. koraiensis and Q. mongolica in the early stage of regeneration in the forest stands.